Ethics for a brave new world - Feinberg, John S. 1946-; Feinberg, Paul D. (Wheaton, IL Crossway, 1993)
Includes bibliographical references and indexes.
Keywords: Huxley, Aldous, -- 1894-1963, -- Brave new world; Social ethics; Christian ethics